2015
DOI: 10.1111/dme.12850
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of C‐peptide have clinical significance for established Type 1 diabetes

Abstract: Aim To determine whether the low C-peptide levels (<50 pmol/l) produced by the pancreas for decades after onset of Type 1 diabetes have clinical significance. Methods We evaluated fasting C-peptide levels, duration of disease and age of onset in a large cross-sectional series (n=1272) of people with Type 1 diabetes. We then expanded the scope of the study to include the relationship between C-peptide and HbA1c control (n=1273), as well as diabetic complications (n=324) and presence of hypoglycaemia (n=323). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
119
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 30 publications
(42 reference statements)
14
119
2
3
Order By: Relevance
“…To the best of our knowledge, this was the first study of the effect of MSC infusion on patients with severe diabetes and our novel data extended previous findings111213 and support the notion that infusion with MSCs benefits T1D patients by preserving β-cell function. Notably, preservation of β-cell function and control of hyperglycemia are crucial for reducing and preventing long-term hyperglycemia-related complication, which is a leading cause of morbidity and mortality of diabetic patients1718. Our findings may aid in design of new therapies for patients with severe T1D.…”
Section: Discussionmentioning
confidence: 78%
“…To the best of our knowledge, this was the first study of the effect of MSC infusion on patients with severe diabetes and our novel data extended previous findings111213 and support the notion that infusion with MSCs benefits T1D patients by preserving β-cell function. Notably, preservation of β-cell function and control of hyperglycemia are crucial for reducing and preventing long-term hyperglycemia-related complication, which is a leading cause of morbidity and mortality of diabetic patients1718. Our findings may aid in design of new therapies for patients with severe T1D.…”
Section: Discussionmentioning
confidence: 78%
“…17, 18, 20 It is known that the rate of decline of β-cell function after diagnosis in T1D is highly variable and many patients retain detectable insulin secretion (as measured by stimulated C-peptide production) for years or decades. 19 The basis for this variability is not understood but is partly a function of age at disease onset as well as the intensity of diabetes management in the early period after diagnosis. 32 Regardless of the mechanism of this variability, those with better preserved C-peptide secretion have lower rates of hypoglycemia and decreased microvascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…17 The original analyses suggested that these clinical benefits were associated with C-peptide levels above a minimum threshold of 0.2 pmol/mL (“responders”), but more recent analyses indicate that reduced rates of hypoglycemia and microvascular complications are observed across a range of C-peptide values with no threshold or breakpoint, 18 suggesting that even very low levels of preserved C-peptide secretion in T1D can confer clinical benefits. 19 …”
Section: Introductionmentioning
confidence: 99%
“…to fully support a clinical benefit for it. However, some experts argue that C-peptide retention is a clinically important endpoint in its own right, pointing to research suggesting that residual C-peptide confers clinical benefits including better long-term glycaemic control [1719]. Nonetheless, our study was designed to answer the question of whether or not GAD therapy should be developed further, so we await optimisation of this vaccine before a robust appraisal of its full clinical benefit can be attempted.…”
Section: Discussionmentioning
confidence: 99%